2008
DOI: 10.1159/000112914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Determinants of Underprescription of Erythropoiesis Stimulating Agents in Pre-Dialysis Patients with Anaemia

Abstract: Background: Inadequate anaemia correction (haemoglobin (Hb) <11 g/dl without receiving an erythropoiesis-stimulating agent (ESA) is common in pre-dialysis patients, but little is known about its determinants. We used data from the French end-stage renal disease (ESRD) registry to investigate these determinants and the patients’ anaemia status 1 year after starting dialysis. Methods: Pre-dialysis anaemia care was studied in 6,271 incident ESRD patients from 13 regions, who were first treated between 2003 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Good management of anaemia in CKD patients has been shown to be associated with decreased morbidity and mortality [24] and a reduced occurrence of cardiovascular complications [25]. Anaemia care was suboptimal here, with appropriate management in 56.2% of cases, but much better than that found in other studies [4,9,10,12]. For example, Bailie et al reported that only 20% of patients with stages 2-5 CKD were receiving epoetin therapy and 13% iron at the time of enrolment [9].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Good management of anaemia in CKD patients has been shown to be associated with decreased morbidity and mortality [24] and a reduced occurrence of cardiovascular complications [25]. Anaemia care was suboptimal here, with appropriate management in 56.2% of cases, but much better than that found in other studies [4,9,10,12]. For example, Bailie et al reported that only 20% of patients with stages 2-5 CKD were receiving epoetin therapy and 13% iron at the time of enrolment [9].…”
Section: Discussionmentioning
confidence: 96%
“…Despite the availability since 1997 of guidelines from the National Kidney Foundation describing how to manage CKD patients, the literature shows that insufficient attention is being paid to the issues outlined above [2][3][4][5][6][7][8][9][10][11][12]. However, most studies reported to date have evaluated the quality of care with reference to no more than a few co-morbid conditions or complications, sometimes only one.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to incident patients experiencing a slight increase in Hb levels during the exposure period, presumably because most of them did not receive ESAs before initiation of dialysis. 15 The higher level of variability may also be explained by a higher prevalence of comorbidities among incident patients. 16 Our findings for residual SD were relatively consistent with previously reported findings.…”
Section: Clinical Epidemiology Wwwjasnorgmentioning
confidence: 99%
“…Sur le registre REIN en 2006, 2 patients sur 3 en IRCT avaient un taux d'hémoglobine inférieur à 11 g/dl à l'initiation du traitement, en dépit de l'accessibilité à l’érythropoïétine, qu'ils soient ou non diabétiques [ 8 , 15 ]. De même que dans une étude précédente [ 16 ], en France, il n'a pas été mis en évidence de lien entre le statut diabétique et l'importance de l'anémie, contrairement à ce qui a pu être observé dans l’étude ACORD (The Anaemia CORrection in Diabetes) [ 17 ]. Le taux de ferritinémie significativement plus bas chez les diabétiques de notre série pourrait y contribuer de sa part (267 ng/ml vs. 343 ng/ml, p= 0,04).…”
Section: Discussionunclassified